FACTORS AFFECTING STUDENT ACCEPTANCE OF EVOLUTION THEORY BASED ON GENDER AND EDUCATIONAL BACKGROUND: a case study in Universitas Islam Madura, Indonesia - Shefa Dwijayanti Ramadani; Lukluk Ibama (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
Evolution is one area on Biology learning that has the most contravention and misconception for many students in various educational regions globally, including Indonesia. This study aimed to identify student's acceptance of the evolutionary theory. The study was conducted using a mixed-method, in which the results of descriptive research were followed by correlational research on the variables studied. Data were collected by using questionnaire and rubric of Measure of Acceptance of The Theory of Evolution (MATE). The results showed that the average MATE score was 65.05, in which the students tended to have a moderate level of the acceptance of the evolutionary theory. The result showed that sex and religious background correlated with students' acceptance of the evolutionary theory, with a contribution of 49.9%. Thus, these results suggest that evolution is a crucial aspect to be considered in teaching evolution, and there must be an effort to overcome the differences in the acceptance of evolutionary theory in students with different gender and educational backgrounds. Three other factors influence student acceptance of the theory of evolution, namely students' misconceptions, beliefs, and understanding of the nature of science. Therefore, identification of students' prior knowledge is needed to determine the factors that influence students' acceptance in a context.